Three-dimensional macro-scale assessment of regional and temporal wall shear stress characteristics on aortic valve leaflets. Issue 6 (25th April 2016) - Cao, K.; BukaČ, M.; Sucosky, P.
Abstract : The aortic valve (AV) achieves unidirectional blood flow between the left ventricle and the aorta. Although hemodynamic stresses have been shown to regulate valvular biology, the native wall shear stress (WSS) experienced by AV leaflets remains largely unknown. The objective of this study was to quantify computationally the macro-scale leaflet WSS environment using fluid–structure interaction modeling. An arbitrary Lagrangian–Eulerian approach was implemented to predict valvular flow and leaflet dynamics in a three-dimensional AV geometry subjected to physiologic transvalvular pressure. Local WSS characteristics were quantified in terms of temporal shear magnitude (TSM), oscillatory shear index (OSI) and temporal shear gradient (TSG). The dominant radial WSS predicted on the leaflets exhibited high amplitude and unidirectionality on the ventricularis (TSM>7.50 dyn/cm 2, OSI < 0.17, TSG>325.54 dyn/cm 2  s) but low amplitude and bidirectionality on the fibrosa (TSM < 2.73 dyn/cm 2, OSI>0.38, TSG < 191.17 dyn/cm 2  s). The radial WSS component computed in the leaflet base, belly and tip demonstrated strong regional variability (ventricularis TSM: 7.50–22.32 dyn/cm 2, fibrosa TSM: 1.26–2.73 dyn/cm 2 ). While the circumferential WSS exhibited similar spatially dependent magnitude (ventricularis TSM: 1.41–3.40 dyn/cm 2, fibrosa TSM: 0.42–0.76 dyn/cm 2 ) and side-specific amplitude (ventricularis TSG: 101.73–184.43 dyn/cm 2  s, fibrosa TSG: 41.92–54.10 dyn/cm 2  s), its temporal variations were consistently bidirectional (OSI>0.25). This study provides new insights into the role played by leaflet–blood flow interactions in valvular function and critical hemodynamic stress data for the assessment of the hemodynamic theory of AV disease.